Ecological role of invertebrates in soil nutrient cycling (Zoological Records and Reviews, 2023)
Soil invertebrates -- encompassing earthworms, Collembola, oribatid mites, enchytraeids, millipedes, isopods, ants, andtermites -- are the principal biological drivers of soil nutrient cycling, organic matter decomposition, and soil structureformation in terrestrial ecosystems. Their collective biomass exceeds that of all terrestrial vertebrates combined, yet theirfunctional roles in nutrient cycling are rarely incorporated into ecosystem management frameworks and remain poorlyquantified relative to microbial decomposers. This review synthesises evidence from 194 primary studies (2005-2023)examining the ecological roles of soil invertebrate groups in nutrient cycling across European terrestrial ecosystems,evaluating six functional mechanisms: litter comminution, soil bioturbation, microbial community modulation, nutrientmineralisation, aggregate formation, and plant-soil feedback mediation. Earthworms contribute a mean 32.4 +- 8.4% ofsoil nitrogen mineralisation in temperate European grasslands and forests, with functional replacement by Collembolaand enchytraeids accounting for an additional 18.4 +- 4.8%. Agricultural intensification -- particularly synthetic fertiliserapplication, tillage, and pesticide use -- reduces soil invertebrate diversity by a mean 44.8 +- 8.4% and functionalbiomass by 58.4 +- 12.4%, with measured nitrogen mineralisation rate declines of 28.4 +- 6.4% in invertebrate-depletedsoils compared to reference grasslands. Rewilding and organic farming practices restore soil invertebrate communitiestowards reference conditions within 8-15 years, recovering 68-84% of reference mineralisation rates. Implications for EUSoil Monitoring Law, Common Agricultural Policy agri-environment scheme design, and Nature Restoration Law soilecosystem restoration targets are discussed.